miR-130b-3p Modulates Epithelial-Mesenchymal Crosstalk in Lung Fibrosis by Targeting IGF-1 - Li, Shuhong (PLoS One, 2016)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and usually lethal fibrotic lung disease with largely unknown etiology and pathogenesis. Evidence suggests microRNAs (miRNA) contribute to pathogenesis of IPF. In this study, we sought to identify miRNA expression signatures and determine the role of miR-130b-3p in lung fibrosis. The miRNA expression profile of the lungs from patients with IPF and normal donors was determined by Affymetrix microarray, and transcriptome with Affymetrix array. The functions and signal pathways as well as miRNA-mRNA networks were established by bioinformatics analysis. Luciferase assays and ELISA were used to confirm the miRNA target gene. The effect of miRNA-transfected epithelium on fibroblast activities was assessed using a co-culture system. The fibroblast activities were determined by qRT-PCR, western blotting, Transwell and BrdU assays. Seven miRNAs were significantly decreased in IPF lungs, with miR-130b-3p being the highest in the miRNA-mRNA network. Insulin-like growth factor (IGF-1) was a target gene of miR-130b-3p in the epithelium. miR-130b-3p inhibition in the epithelium induced collagen I expression and enhanced the proliferation and migration ability of fibroblast in co-culture systems, which mimicked the functions of exogenous IGF-1 on fibroblasts. Neutralizing IGF-1 with an antibody significantly reduced the modulatory effects of miR-130b-3p inhibitor-transfected epithelium on the activation of fibroblasts. Our results show that miR-130b-3p was downregulated in IPF lungs. miR-130b-3p downregulation contributed to the activation of fibroblasts and the dysregulated epithelial-mesenchymal crosstalk by promoting IGF-1 secretion from lung epithelium, suggesting a key regulatory role for this miRNA in preventing lung fibrosis.